Effect of personalized care based on OPT model on perceived control and quality of life among patients with breast cancer - Rahman, Rabigul; Mamat, Parida; Wang, Haiyan; Nurtai, Mili; Mahsut, Maynur; Ahmat, Zulhumar; Siyit, Mukadas; Shang, Hongmei; Zhang, Xiaoyan (Frontiers in Public Health, 2023)
Introduction: Patients with breast cancer (BC) after surgery are prone to negative physiological and psychosocial discomforts which cause the poor quality of life (QoL) among the patients. Therefore, how to improve the disease management ability of BC patients and to alleviate these cancer-related negative experience are particularly important. This study purpose to explore the potential effects of personalized care based on OPT model on the perceived control and the QoL among patients with BC, and to provide effective clinical nursing intervention for BC patients. Methods: In this study, nonsynchronous controlled experiments were carried out on patients with BC, and the patients were randomly allocated to the control (n = 40) and intervention (n=40) groups. The patients in the control group were given routine care; while the patients in the intervention group were given personalized care based on OPT model. The perceived control ability and QoL of the two groups were measured before and after the intervention. Results: There were no significant differences in the total score of cancer experience and control efficacy of BC patients between the control group (61.15 ± 5.659, 41.80 ± 4.702) and the intervention group (60.58 ± 7.136, 42.15 ± 5.550) before intervention (P > 0.05). After the intervention, the total score of cancer experience in the intervention group (54.80 ± 8.519) was significantly lower than that in the control group (59.575 ± 7.331), with significant differences (P < 0.05). The total score of control efficacy in the intervention group (49.78 ± 6.466) was significantly higher than that in the control group (43.32 ± 6.219), with significant differences (P < 0.05). Compared with the control group, patients in intervention groups showed significant improvement in QoL after the intervention (P < 0.05) . Conclusions: Personalized care based on OPT model plays a significant role in improving the level of perceived control and the QoL among patients with BC.